An Efficient Electronic English Auction System with a Secure On-Shelf Mechanism and Privacy Preserving. (4th May 2016) - Zhong, Hong; Li, Song; Cheng, Ting-Fang; Chang, Chin-Chen
Abstract : With the rapid development of the Internet, electronic commerce has become more and more popular. As an important element of e-commerce, many Internet companies such as Yahoo! and eBay have launched electronic auction systems. However, like most electronic commerce products, safety is an important issue that should be addressed. Many researchers have proposed secure electronic auction mechanisms, but we found that some of them do not exhibit the property of unlinkability, which leads to the leakage of users' privacy. Considering the importance of privacy preservation, we have designed a new auction mechanism. Through symmetrical key establishment in the registration phase, all messages transmitted over the Internet would be protected and, meanwhile, achieve the property of unlinkability. The security analysis and performance analysis show that our protocol fulfills more security properties and is more efficient for implementation compared with recent works.